Books are forever: Early life conditions, education and lifetime income - Giorgio Brunello; Guglielmo Weber; Christoph T. Weiss (Institute for the Study of Labor (IZA), 2012)
In this paper we estimate the effect of education on lifetime earnings in Europe, by distinguishing between individuals who lived in rural or urban areas during childhood and between individuals who had access to many or few books at age ten. We instrument years of education using reforms of compulsory education in nine different countries, and find that individuals in rural areas were most affected by the reforms while individuals with many books at home mostly benefited from education. Our main result is that books at home at age ten have had long-lasting beneficial effects on the individuals who were pushed by the reforms to increase their years of education.
urn:nbn:de:101:1-201206146614
Keywords: J24; 330; education; lifetime income; early conditions; Europe; Sozialisation; Kognition; Bildungschancen; Bildungsertrag; Erwerbsverlauf; Ländlicher Raum; Europa